Codonopsis pilosula Polysaccharides Exert Antiviral Effect Through Activating Immune Function in a Macrophage Model of Bovine Viral Diarrhea Virus Infection - Xiaowei Feng; Lei Wang; Jingyan Zhang; Haipeng Feng; Xiaoliang Chen; Junyan Wang; Mingxian Shi; Kang Zhang; Jianxi Li (Veterinary Sciences)
Bovine viral diarrhea (BVD) is a common viral disease in cattle that causes huge economic losses in naïve herds that are introduced to bovine viral diarrhea virus (BVDV). Currently, there are no available anti-BVDV drugs due to the variety and mutability of strains; therefore, developing new anti-BVDV drugs is of great significance. The aim of this study was to investigate the anti-BVDV effects and immunomodulatory activities of Codonopsis pilosula polysaccharides (CPPs) in BVDV-infected bovine macrophage (BoMac) cells. CPPs directly inactivated BVDV particles and intervened in BVDV absorption process. The immunity suppression resulting from BVDV in BoMac cells was restored by CPPs, as was verified by phagocytosis increase, the expression up-regulation of cell surface co-stimulatory molecules (CD40, CD80, and CD86), and antigen-presenting function recovery. Furthermore, the expressions of cytokines including TNF-α, IFN-γ, IL-6, IL-18, IL-1β, Caspase-3, Bim, and Bcl-xL at the mRNA and proteins levels were modulated, and a reduction in the apoptosis rate was observed, which demonstrates that CPPs attenuated inflammation and apoptosis induced by BVDV. Collectively, our findings reveal new pharmacological properties of CPPs, which exert anti-BVDV efficacy and regulate immune injury induced by BVDV in BoMac cells, indicating that CPPs are a potential option for BVDV prevention in clinical application.